The Theory of Planned Behavior and Pro-Environmental Behavior among Students - EFFENDI, Mohamad Irhas; SUGANDINI, Dyah; SUKARNO, Agus; KUNDARTO, Muhamad; ARUNDATI, Rahajeng (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).05, 2020)
This study aims to analyze pro-environmental behavior that is influenced by perceived behavioral control, subjective norms, environmental attitude, and intention. This research is based on the Theory of Planned Behavior. This study uses students as respondents because students are young people who are most responsible for environmental preservation both now and in the future. Higher education is also often the foundation for various student social movements when it comes to values and pro-environment associations. This research was conducted to address empirical issues related to the relationship between attitudes to pro-environmental behavior which is still being debated. This argument becomes an important basis for analyzing the level and relationship of pro-environmental behavior and students' attitudes towards environmental sustainability. The intention is the influencer's biggest for the behavior of pro-environmental students, but not all research yields the same answer depending on the behavior and case, as well as the pro-environment attitude. This study used 250 student respondents. The data analysis tool used is PLS-SEM 3.2.8. The results of this study explain that pro-environmental behavior can be influenced by perceived behavioral control and intention to behave pro-environment. Also, the results of this study showed that perceived behavioral control, subjective norms, and attitudes also affect intention.